Faceted Inuit-European contact in southern Labrador - Stopp, Marianne (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2015)
Archaeological evidence from three sites excavated or tested between 2009 and 2013 is shown to be valuable for interpreting the diverse nature of the early Inuit-European contact zone in southern Labrador. Beginning in the late 17th century, French and then English archival records for the region describe relations with Inuit that were motivated by trade but that repeatedly devolved into violence. Indeed, if only the historical records were available we would learn little of the range of Inuit responses to colonialism other than its context of aggression. The archaeological data, in contrast, decolonize this history and point to a more nuanced contact landscape than suggested by the written records, with clues to varied cultural intersections, and Inuit resilience and persistence.